PANJANG, BOBOT TRAKTUS DIGESTIVUS DAN BOBOT TUBUH PUYUH (Coturnix coturnix japonica) SETELAH PENAMBAHAN TEPUNG KUNYIT(Curcuma longa) DAN TEPUNG IKAN PADA PAKAN - Siti Zulaikhah; Koen Praseno; Tyas Rini Saraswati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Quail age and digestive activity continuously contribute to decreased tissue function and digestion , causing tissue damage . Turmeric contains essential oils and curcumin . Fish meal is high in protein . This sstudy of this research was to determinate the effect of turmeric powder and fish meal after the long decline of productivity, digestive tract weights and body weight. This research used Completely Randomized Design ( CRD ) and analyzed by ANOVA. Showed significant difference when tested further by Duncan's test at 95% significance level. Animals were used 60 quails grouped into 4 treatments , with 15 replicates , the study concludes on the ninth month . Treatment given P0 : Group quail fed standard , P1 : Group quail fed standard and turmeric 54mg / head / day , P2 : quail group given standard feed plus 85 % fish meal, 15 % , P3 : Group quail fed plus standard feed fish meal and turmeric . Treatment was given at the age of quail 7-8 months . The main parameters measured were length, weight of digestive tract and body weight . Supporting parameters measured were feed intake, and feed conversion . The results are length, weight and body weight digestive tract there is not a real difference. Consumption and feed conversion showed real differences. The addition of turmeric, fish meal and combination of tumeric and fish meal are not potentially add length digestive tract weights and body weight.Keywords: Quail (Coturnix coturnix japonica), turmeric, fish meal, the length, the weight of digestive tract and body weight